2021
DOI: 10.1093/geronb/gbab009
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Social Distancing Measures and Loneliness Among Older Adults

Abstract: Objectives In response to the COVID-19 pandemic, older adults are advised to follow social distancing measures to prevent infection. However, such measures may increase the risk of loneliness. The current study aimed to investigate (1) whether social distancing measures, particularly limiting close social interactions, are associated with loneliness among older adults, and (2) whether the association between social distancing measures and loneliness is moderated by sociodemographic characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 35 publications
7
50
1
Order By: Relevance
“…Individuals at higher risk for severe illness, those with pre-existing conditions (hypertension, pulmonary disease, diabetes, and cardiovascular disease), racial/ethnic minorities, older age, and male sex, may also be more likely to experience loneliness and social isolation [ 10 ]. Studies have suggested that COVID-19 preventive behaviors may result in greater odds of reporting loneliness and social isolation [ 11 , 12 , 13 ]. For instance, a population-based study in the United States (U.S.) examining the impact of COVID-19 social distancing and preventive behaviors found that 54% of participants reported loneliness [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals at higher risk for severe illness, those with pre-existing conditions (hypertension, pulmonary disease, diabetes, and cardiovascular disease), racial/ethnic minorities, older age, and male sex, may also be more likely to experience loneliness and social isolation [ 10 ]. Studies have suggested that COVID-19 preventive behaviors may result in greater odds of reporting loneliness and social isolation [ 11 , 12 , 13 ]. For instance, a population-based study in the United States (U.S.) examining the impact of COVID-19 social distancing and preventive behaviors found that 54% of participants reported loneliness [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although older adults may have an advantage relative to younger adults, it is unclear whether older adults across the globe experienced increases in loneliness during COVID-19. For example, Choi et al (2021) found that US older adults who limited social interactions during the early stages of the pandemic (April to May 2020) were at higher risk for loneliness, but Luchetti et al (2020) found no sustained increase of loneliness among older Americans (Luchetti et al, 2020). A qualitative US study found that older people who had lived with persistent loneliness before the pandemic did not report feeling lonelier than before COVID-19 (Bundy et al, 2021).…”
Section: Older Adults' Loneliness During Covid-19mentioning
confidence: 99%
“…This trend may have been particularly problematic for older adults with fewer family ties-such as unpartnered or childless older adults. Although there is a recent explosion of studies examining loneliness during COVID-19, with several studies focused on older adults (e.g., Bundy et al, 2021;Choi et al, 2021;Macdonald & Hulur, 2021;van Tilburg et al 2021), no study to date has specifically examined the loneliness risk of unpartnered older adults and childless older adults during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic has exacerbated loneliness and social isolation, likely due to increased susceptibility and seriousness of viral risk (Kotowal et al, 2021;Shahid et al, 2020), combined with physical and social distancing (especially stay-at-home policies) (Wister & Speechley, 2020). Most of the longitudinal studies comparing levels of loneliness pre and peri-pandemic have reported higher levels of loneliness during the beginning periods of the pandemic (Kotowal et al, 2021;Stoltz et al, 2021); however, some studies show a plateauing or even decrease over the course of the pandemic (Choi et al, 2021;Luchetti et al, 2020). Evidence for the impact of the pandemic on social isolation has been equivocal (Herrera et al, 2021;Kotwal et al, 2021;Strutt et al, 2021).…”
Section: Introductionmentioning
confidence: 99%